(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Poly(Methyl Methacrylate) PMMA/Organically Modified Montmorillonite (O-MMT) composite microfibers membrane coated with TiO_2 has significant advantages in cationic dyes adsorption and can break down the adsorbed dyes under UV radiation, which is quite useful in water treatment. In this work, PMMA/O-MMT composite microfibers were firstly prepared by emulsion polymerization combined with electrospinning, and then coated by nanosize TiO_2 using RF magnetron sputtering. The effects of TiO_2 sputter coating on morphology and surface modulus was characterized by Scanning Electron Microscope (SEM) and Atomic Force Microscopy (AFM), while the wetting behaviour was studied by drop shape analyzer. The photocatalytic degradation of methylene blue was tested under UV radiation and the properties of the treated and untreated samples were compared. It was observed from SEM images that TiO_2 was well dispersed and deposited on the surface of PMMA/O-MMT microfibers, while the AFM results showed increase in the surface modulus after TiO_2 coating. Besides, the wettability of the microfibers membrane coated with TiO_2 was altered, which facilitated water treatment in practical use. Furthermore, the PMMA/O-MMT microfibers membrane coated with TiO_2 performed well in photocatalytic degradation of methylene blue. In conclusion, PMMA/O-MMT composite microfibers membrane coated with TiO_2 was quite promising in water treatment.